Relationships between growth of the preovulatory follicle and gestation success in lactating dairy cows - Vasconcelos, José Luiz Moraes [UNESP]; Pereira, M. H. C.; Meneghetti, M.; Dias, C. C.; SaFilho, O. G.; Peres, R. F. G.; Rodrigues, A. D. P.; Wiltbank, M. C. (Brazilian Coll Animal Reproduction, 2013)
This report summarizes three studies conducted with lactating dairy cows aiming to increase pregnancy rates to fixed time artificial insemination (TAI) protocols. Experiment 1 was designed to determine if changing the timing of PGF2 alpha treatment during an E2/P4-based program would affect fertility to TAI or fixed-time embryo transfer (TET). In experiment 2, pregnancy rates to AI were compared following synchronized ovulation using two protocols that have been developed to reduce the period between follicular wave emergence and TAI. The Ovsynch-type protocol utilizes GnRH to synchronize the follicular wave by inducing ovulation of a dominant follicle at the beginning of the protocol, and to synchronize ovulation at the end of the protocol allowing TAI. In contrast, E2/P4-based protocols utilize E2 products in the presence of P4 to induce atresia of antral follicles and synchronize emergence of a new follicular wave. At the end of E2/P4-based protocol another E2 treatment in the absence of P4 is used to induce LH release and synchronize ovulation and allow TAI. Experiment 3 was designed to determine whether increasing the length time interval with reduced circulating P4 (proestrus) would increase fertility in a TAI program that utilized E2 and P4 to synchronize ovulation of cycling, lactating dairy cows. The overall conclusions are that circulating concentrations of progesterone and estradiol prior to and circulating concentrations of progesterone following ovulation can affect fertility in cattle. In addition, small increases in P4 concentrations near the time of AI, due to lack of complete CL regression, result in reductions in fertility. Earlier treatment with PGF2 alpha should allow greater time for CL regression, an increase in estradiol and subsequent reductions in circulating P4 that could be critical for fertility. Optimization of follicle size in TAI programs is clearly an intricate balance between oocyte quality, adequate circulating E2 near AI, and adequate circulating P4 after AI.